Report on the Plans and Priorities of the Department of Justice Canada 2006-2007 - (:unkn) unknown (My University, 2016)
Canada’s laws affect virtually every aspect of our political, social, and economic life. They are the bedrock of our proud tradition of safety and security, ensuring that all Canadians - particularly the most vulnerable members of society - can live in safe, healthy communities.